The Evolvement of International Business Education - Daniels, John D.; Radebaugh, Lee H. (Journal of International Business Studies, 1975)
The 1974 curriculum survey for the Academy of International Business shows some departures in course offerings since the 1969 survey. With changes in AACSB accreditation standards, further evolvement is anticipated.